1989
DOI: 10.1002/cne.902830302
|View full text |Cite
|
Sign up to set email alerts
|

Bed nucleus of the stria terminalis: Cytoarchitecture, immunohistochemistry, and projection to the parabrachial nucleus in the rat

Abstract: The bed nucleus of the stria terminalis (BST) sends a dense projection to the parabrachial nucleus (PB) in the pons. The BST contains many different types of neuropeptidelike immunoreactive cells and fibers, each of which exhibits its own characteristic distribution within cytoarchitecturally distinct BST subnuclei. Corticotropin releasing factor (CRF)-, neurotensin (NT)-, somatostatin (SS)-, and enkephalin (ENK)-like immunoreactive (ir) neurons are particularly numerous within areas of the BST that project to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
240
0
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 335 publications
(262 citation statements)
references
References 49 publications
19
240
0
3
Order By: Relevance
“…Many Fos-positive cells in this region were found among CRH-containing processes, and occasional small cells in the dorso-and central lateral subnuclei were double-stained for Fos and CRH after CLP. The CRHcontaining terminals in the lateral parabrachial region originate in part from the medial and commissural subnuclei of the NTS and also from the bed nucleus of the stria terminalis (Moga et al, 1989), the central nucleus of the amygdala (Moga and Gray, 1985), and the lateral hypothalamus . The enhanced detection of CRH in the NTS and the colocalization of CRH with Fos in the bed nucleus after CLP suggest that the projections from these areas to the parabrachial nucleus are activated during sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Many Fos-positive cells in this region were found among CRH-containing processes, and occasional small cells in the dorso-and central lateral subnuclei were double-stained for Fos and CRH after CLP. The CRHcontaining terminals in the lateral parabrachial region originate in part from the medial and commissural subnuclei of the NTS and also from the bed nucleus of the stria terminalis (Moga et al, 1989), the central nucleus of the amygdala (Moga and Gray, 1985), and the lateral hypothalamus . The enhanced detection of CRH in the NTS and the colocalization of CRH with Fos in the bed nucleus after CLP suggest that the projections from these areas to the parabrachial nucleus are activated during sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BNST inactivation during the stressor did not prevent the corticosterone response. These results are somewhat unexpected given the projections from the BNST to hypothalamic and brainstem areas associated with the stress response (Gray, Carney, & Magnuson, 1989;Gray & Magnuson, 1987;Han & Ju, 1990;Moga, Saper, & Gray, 1989;Sawchenko & Swanson, 1983;Silverman, Hoffman, & Zimmerman, 1981;Sofroniew, 1983). Moreover, others have shown that electrical stimulation of the BNST can alter plasma corticosterone levels (Dunn, 1987), and that lesions of the BNST prevent the corticosterone response in contextual, but not cued, fear conditioning (Sullivan, Apergis, Bush, Johnson, Hou, & LeDoux, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The BNST is a primary target of the amygdala (de Olmos et al, 1985;Sun et al, 1991;Alheid et al, 1995), and both the BNST and the amygdala share almost identical brainstem target areas implicated in stress and anxiety responses (Schwaber et al, 1980;Takeuchi et al, 1982Takeuchi et al, , 1983Sofroniew, 1983;Swanson et al, 1984;Veening et al, 1984;Holstege et al, 1985;Magnuson, 1987, 1992;Moga et al, 1989). Interestingly, some of the projections to the amygdala (cf.…”
Section: Implications For a Possible Distinction Between Fear And Anxmentioning
confidence: 99%